Development of a performance measurement framework for SMEs - Sousa, Sérgio (2010)
Quality gurus all recognise the importance of measurement to track progress and ensure quality improvement according to an accepted plan. They emphasise the use of local measures for evaluating performance because of the ease with which a standard can be established. To measure quality, all areas of an organisation and its environment must be addressed. A performance measurement system (PMS) must contribute to and be integrated with other management objectives. In addition, the benefits of using such a system should outweigh its cost. By integrating quality with dimensions of company performance related with core, support and management processes, and considering the constraints associated with small and medium enterprises (SMEs), a framework to foster their performance was developed. The aim was to provide a strategy for implementing various quality measurement tools as part of a continuous improvement programme. The resultant framework is also a means of complying with the associated principles of ISO 9001. Overall, it is argued that the maturity of an SME affects the success of PMSs and quality management systems (QMSs). Finally, this work attempts to bridge the gap between theory and practice by providing SMEs with a framework to help them improve, and thus become more competitive and sustainable.